A dipeptide transporter from the arbuscular mycorrhizal fungus Rhizophagus irregularis is upregulated in the intraradical phase - Belmondo, Simone; Fiorilli, Valentina; Pérez-Tienda, Jacob; Ferrol, Nuria; Marmeisse, Roland; Lanfranco, Luisa (Frontiers in Plant Science, 2014)
Arbuscular mycorrhizal fungi (AMF), which form an ancient and widespread mutualistic symbiosis with plants, are a crucial but still enigmatic component of the plant microbiome. Nutrient exchange has probably been at the heart of the success of this plant-fungus interaction since the earliest days of plants on land. To characterize genes from the fungal partner involved in nutrient exchange, and presumably important for the functioning of the AM symbiosis, genome-wide transcriptomic data obtained from the AMF Rhizophagus irregularis were exploited. A gene sequence, showing amino acid sequence and transmembrane domains profile similar to members of the PTR2 family of fungal oligopeptide transporters, was identified and called RiPTR2. The functional properties of RiPTR2 were investigated by means of heterologous expression in Saccharomyces cerevisiae mutants defective in either one or both of its di/tripeptide transporter genes PTR2 and DAL5. These assays showed that RiPTR2 can transport dipeptides such as Ala-Leu, Ala-Tyr or Tyr-Ala. From the gene expression analyses it seems that RiPTR2 responds to different environmental clues when the fungus grows inside the root and in the extraradical phase.